I-125 seeds brachytherapy combined with immunotherapy for MET amplification in non-small cell lung cancer from clinical application to related lncRNA mechanism explore: a case report - Yang, Mingxing; You, Yuanli; Wang, Xiuqing; Dong, Wen (Frontiers in Cell and Developmental Biology, 2023)
Advanced non-small cell lung cancer (NSCLC) with MET amplification primarily relies on MET inhibitors for treatment, but once resistance occurs, the available treatment options are limited and the prognosis is typically poor. A 57-year-old man with advanced NSCLC and C-MET amplification was initially treated with crizotinib but developed progressive disease. After the antirotinib treatment, he achieved a partial response for a year. Genetic testing showed high PD-L1 expression, and he was treated with pembrolizumab and chemotherapy for 3 months, with partial response. Maintenance therapy with pembrolizumab and local I-125 seeds brachytherapy (ISB) was given after the lung lesion progressed but other lesions remained stable. The therapy resulted in significant resolution of the right upper lung lesion. It demonstrates the effectiveness of ISB-ICI combination in treating MET amplification advanced NSCLC. Ongoing research and treatment innovation are important in managing advanced NSCLC with complex genetic aberrations. To explore the candidate mechanism of ISB therapy response, we download public genetic data and conduct different expression Lncrnas analysis and pathway analysis to discover radiotherapy related sensitive or resistance lncRNAs and pathways, we found that AL654754.1 is a key lncRNA with radiotherapy response, and it also include in classical p53 and Wnt signaling pathway. Overall, the clinical case reports, combined with the exploration of underlying mechanisms, provide positive guidance for the precise treatment of lung cancer.